Pd modified prussian blue frameworks: Multiple electron transfer pathways for improving catalytic activity toward hydrogenation of nitroaromatics - Zhang, Kaiqiang; Cha, Joo Hwan; Jeon, Se Yeon; Kirlikovali, Kent O.; Ostadhassan, Mehdi; Rasouli, Vamegh; Farha, Omar K.; Jang, Ho Won; Varma, Rajender S.; Shokouhimehr, Mohammadreza (ELSEVIER, 2020)
Prussian blue analogs (PBAs) exhibit potential as low-cost and eco-friendly nanocatalysts that can be fabricated with ease. However, the PBA framework structure suffers from poor electronic conductivity, which limits the catalytic efficiency for this class of materials. Noble metals represent an alternative class of materials that display inherent catalytic activity but suffer from aggregation, ultimately reducing the amount of accessible catalytic sites. Herein, we demonstrate a combinatory approach that circumvents the known disadvantages with these classes of catalytic materials in which PBA-supported nanocatalysts were synthesized. These composite materials exhibit excellent catalytic activity for the reduction of nitroaromatics to aminoaromatics while displaying longterm cycling stability, which is attributed to the availability of multiple electron transfer pathways. Overall, this work opens the study on the assembly of PBA-supported heterogeneous nanocatalysts and potentially paves the way toward future applications.
Keywords: METAL-ORGANIC FRAMEWORK; PALLADIUM NANOPARTICLES; REDUCTION; HEXACYANOCOBALTATE; ANALOGS; HEXACYANOFERRATE; NITROARENES; EFFICIENT; MOF; NANOCRYSTALS